A transatlantic perspective on the integration of immuno-oncology prognostic and predictive biomarkers in innovative clinical trial design. (October 2018) - Morfouace, M.; Hewitt, S.M.; Salgado, R.; Hartmann, K.; Litiere, S.; Tejpar, S.; Golfinopoulos, V.; Lively, T.; Thurin, M.; Conley, B.; Lacombe, D.
Abstract: Immuno-therapeutics aim to activate the body's own immune system against cancer and are one of the most promising cancer treatment strategies, but currently limited by a variable response rate. Biomarkers may help to distinguish those patients most likely to respond to therapy; they may also help guide clinical decision making for combination therapies, dosing schedules, and determining progression versus relapse. However, there is a need to confirm such biomarkers in preferably prospective clinical trials before they can be used in practice. Accordingly, it is essential that clinical trials for immuno-therapeutics incorporate biomarkers. Here, focusing on the specific setting of immune therapies, we discuss both the scientific and logistical hurdles to identifying potential biomarkers and testing them in clinical trials.